Dependence of proteoglycan induced arthritis in BALB/c mice on the development of autoantibodies to high density proteoglycans. Issue 8 (August 1992) - Wooley, P H; Siegner, S W; Whalen, J D; Karvonen, R L; Fernández-Madrid, F
Abstract : BALB/c mice were immunised with high or low density native human cartilage proteoglycans, or the respective core proteins obtained from chondroitin ABC lyase digestion. Mice injected with high density native proteoglycans developed arthritis whereas mice injected with low density proteoglycans or with core proteins did not. Analysis of the immune response by enzyme linked immunosorbent assay (ELISA) and western blot showed a stronger and more polyspecific response in animals injected with low density proteoglycans compared with mice with arthritis which had been injected with high density proteoglycans. Autoantibodies to mouse high density proteoglycans were only present in mice injected with native human high density proteoglycans, however. The data suggest that an arthritogenic epitope lies within the glycosaminoglycan rich region of the native proteoglycan molecule, which may induce an autoantibody response and subsequently arthritis in BALB/c mice.